2021
DOI: 10.1136/bmjopen-2020-039981
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a hydrogel dressing as an analgesic adjunct to first aid for the treatment of acute paediatric burn injuries: a prospective randomised controlled trial

Abstract: ObjectiveTo compare the effectiveness of two acute burn dressings, Burnaid hydrogel dressing and plasticised polyvinylchloride film, on reducing acute pain scores in paediatric burn patients following appropriate first aid.DesignSingle-centre, superiority, two-arm, parallel-group, prospective randomised controlled trial.Participants and settingPaediatric patients (aged ≤16) presenting to the Emergency Department at the Queensland Children’s Hospital, Brisbane, Australia, with an acute thermal burn were approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…During cooling with hydrogels, the obtained temperature is about 20.5 °C on the surface of the wound, whereas at a depth of 1–3 mm it is about 33 °C [ 14 ]. What is more, these products provide an analgesic effect and can be safely used as a first aid dressing even in pediatric patients [ 22 ] ( Figure 3 ). The water content in hydrogels is important in cooling, as water stabilizes the temperature of the wound.…”
Section: Burn Wound Coolingmentioning
confidence: 99%
“…During cooling with hydrogels, the obtained temperature is about 20.5 °C on the surface of the wound, whereas at a depth of 1–3 mm it is about 33 °C [ 14 ]. What is more, these products provide an analgesic effect and can be safely used as a first aid dressing even in pediatric patients [ 22 ] ( Figure 3 ). The water content in hydrogels is important in cooling, as water stabilizes the temperature of the wound.…”
Section: Burn Wound Coolingmentioning
confidence: 99%
“…Previous acute paediatric burn RCTs have shown that theoretical frameworks for feasibility are often unachievable 6 15–18. Given the specificity of the type of burn (burns that conform to a PICO dressing), it is likely that eligible participants form a small sub cohort.…”
Section: Methodsmentioning
confidence: 99%
“…Previous acute paediatric burn RCTs have shown that theoretical frameworks for feasibility are often unachievable (27,(29)(30)(31)(32). Given the speci city of the type of burn (signi cant hand and/or foot burns), it is likely that eligible participants will form a small subcohort.…”
Section: Outcomes Pilot Trial Primary Outcomesmentioning
confidence: 99%